Agroforestry homegardens: bibliometric analysis for a 35 year period of scientific production (1984-2019) (Research, Society and Development, 2020)
Bibliographic research is of fundamental importance to facilitate the elaboration of theoretical arguments allowing the construction of knowledge and the identification of the best works among so many productions. The objective of this research was to carry out a bibliometric analysis of publications on agroforestry yards over a period of 35 years. Articles were selected, with the theme of agroforestry yards published between the years 1984 to 2019, in the following databases: Periodicos CAPES, Scielo, Springer, Google Scholar and ResearchGate. After conducting searches using the keywords previously defined, 181 references were defined, being higher in the years 2013 to 2019, already in relation to the journals in which the publications were found, and the Agroforestry Systems (51) was the greatest amount. Among the articles researched, we can highlight Brazil with 49.7% of the research carried out, followed by India and Mexico (7.9%). In the keywords count the most frequent were: Agroforestry, homegardens and diversity. Publications related to agroforestry homegardens have shown positive growth over the years, having their highest peak between the years 2013 to 2018. In addition, international publications were more prominent than national ones, with studies carried out mainly in countries like India and Mexico.